Cardioneuroablation for vasovagal syncope and atrioventricular block: A step‐by‐step guide. (9th April 2022) - Aksu, Tolga; Gupta, Dhiraj; D'Avila, Andre; Morillo, Carlos A.
Abstract: Catheter‐based cardioneuroablation is increasingly being utilized to improve outcomes in patients with vasovagal syncope and atrioventricular block due to vagal hyperactivity. There is now increasing convergence among enthusiasts on its various aspects, including patient selection, technical steps, and procedural end‐points. This pragmatic review aims to take the reader through a step‐by‐step approach to cardioneuroablation: we begin with a brief overview of the anatomy of intrinsic cardiac autonomic nervous system, before focusing on the indications, preprocedure and postprocedure management, necessary equipment, and its potential limitations.